An improved hierarchical lossless text compression algorithm - Chia-Yuan Teng; Neuhoff, D.L. (Proceedings DCC '95 Data Compression Conference, 1995)
Several improvements to the Bugajski-Russo N-gram algorithm are proposed. When applied to English text these result in an algorithm with comparable complexity and approximately 10 to 30% less rate than the commonly used COMPRESS algorithm.